Prospective Cohort Study in Alport Syndrome Patients Under Standard Therapy - Oliver Gross; Michelle N. Rheault; James Simon; Bertrand Knebelmann; Yuqian Shen; Qi Zhang; Ali Hariri; Julie Lin; Shiguang Liu; Clifford E. Kashtan (Kidney International Reports)
Introduction: Patients with Alport syndrome (AS), a common genetic kidney disease, exhibit variable rates of decline in kidney function. Consequently, this global, multicenter, prospective observational study aimed to generate data useful for designing future interventional trials. Methods: The study included patients aged 12 to 65 years with a confirmed diagnosis of AS and estimated glomerular filtration rate (eGFR) of 45 to 90 ml/min. For up to 120 weeks in 12-weekly intervals, blood and urine samples, patient and family history, genotype, adverse events (AEs), medications, and patient-related outcome data were collected under International Conference on Harmonization-Good Clinical Practice (ICH-GCP) standards. Results: Out of 165 patients enrolled, 101 (61.2%) were classified as X-linked (62.4% females, 37.6% males) and 32 (19.4%) as autosomal (recessive or dominant) inheritance. Baseline mean eGFR was 64 ml/min per 1.73 m2, and yearly eGFR slope in ml/min per 1.73 m2 was −2.94 (−6.7 in X-linked males, 0.6 in X-linked females, −1.66 in heterozygous autosomal patients). Baseline urine albumin-to-creatinine ratio (UACR) was the best predictor for rapid loss of eGFR with a yearly eGFR slope of −10.16 ml/min per 1.73 m2 in patients with UACR > 1 g/g compared with−0.90 ml/min per 1.73 m2 if UACR was ≤ 1.0 g/g. Out of 353 AEs, only 26 (7.4%) were related to AS. In addition to UACR, neutrophil gelatinase-associated lipocalin, clusterin, and kidney injury molecule-1 correlated with the eGFR slope. Conclusion: In patients with AS receiving standard of care, rapid decline in kidney function strongly correlates with UACR and AEs related to the underlying medical condition are rare. Both findings enrich the design of future interventional trials.